Update in the understanding of altitude-induced limitations to performance in team-sport athletes - Billaut, F.; Aughey, R. J. (British Journal of Sports Medicine, 2013)
The internationalism of field-based team sports (TS) such as football and rugby requires teams to compete in tournaments held at low to moderate altitude (~1200-2500 m). In TS, acceleration, speed and aerobic endurance are physical characteristics associated with ball possession and, ultimately, scoring. While these qualities are affected by the development of neuromuscular fatigue at sea level, arterial hypoxaemia induced by exposure to altitude may further hinder the capacity to perform consecutive accelerations (CAC) or sprint endurance and thereby change the outcome of a match. The higher the altitude, the more severe the hypoxaemia, and thus, the larger the expected decline in aerobic endurance, CAC and match running performance. Therefore, it is critical for athletes and coaches to understand how arterial hypoxaemia affects aerobic endurance and CAC and the magnitude of decline they may face at altitude for optimal preparation and increased chances of success. This mini review summarises the effects of acute altitude/hypoxia exposure on aerobic endurance, CAC and activity profiles of TS athletes performing in the laboratory and during matches at natural altitude, and analyses the latest findings about the consequences of arterial hypoxaemia on the relationship between peripheral perturbations, neural adjustments and performance during repeated sprints or CAC. Finally, we briefly discuss how altitude training can potentially help athletes prepare for competition at altitude.